Characterizing couple dysfunction in borderline personality disorder - Miano, Annemarie; Dziobek, Isabel; Röpke, Stefan (Journal of personality disorders, 2020)
Relationship dysfunction is a key criterion of borderline personality disorder (BPD). Nevertheless, little is known about the characteristics of romantic relationship functioning in BPD. In this study, couples in which the women were diagnosed with BPD (BPD couples) and healthy control couples (HC) were compared in their perceived relationship characteristics (e.g., relationship quality) and interpersonal experience variables (e.g., attachment). The hypothesis was tested that insecure attachment styles account for group differences in relationship characteristics. Variables were measured by self-report. Romantic relationships were appraised as more negative and conflictual by both members of BPD couples compared to HC. The perception of women with BPD was often more negative than that of their male partners, indicating potential biases in BPD patients' relationship evaluation. Insecure attachment styles only partially explained group differences in relationship characteristics, showing that attachment style is one, but not the only predictor of decreased relationship functioning in BPD couples.
Gesehen am 10.06.2020